2011
DOI: 10.1021/jp2015929
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Heterogeneity within the Michaelis Complex of Lactate Dehydrogenase

Abstract: A series of isotope edited IR measurements, both static as well as temperature jump relaxation spectroscopy, are performed on lactate dehydrogenase (LDH) to determine the ensemble of structures available to its Michaelis complex. There clearly has been a substantial reduction in the number of states available to the pyruvate substrate (as modeled by the substrate mimic, oxamate) and NADH when bound to protein compared to dissolved in solution, as determined by the bandwidths and positions of the critical C2=O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 27 publications
7
61
0
Order By: Relevance
“…In this kinetic scheme, which is in agreement with various results, 7,8,15 the encounter complex, presumed to have an “open”-loop conformation, leads to two other conformations of the Michaelis complex, labeled inactive and active, which are probably of “closed”-loop conformations with varying loop structure and an atomic arrangement in the active site. The two closed conformations do not appear to directly interconvert but do so via the encounter complex.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In this kinetic scheme, which is in agreement with various results, 7,8,15 the encounter complex, presumed to have an “open”-loop conformation, leads to two other conformations of the Michaelis complex, labeled inactive and active, which are probably of “closed”-loop conformations with varying loop structure and an atomic arrangement in the active site. The two closed conformations do not appear to directly interconvert but do so via the encounter complex.…”
Section: Resultssupporting
confidence: 91%
“…Because oxamate is a non-reactive species, the arrow labeled “chemical step” purely reflects the presumed relative reactivity between the observed conformations (cf. refs 5 and 15). …”
Section: Figurementioning
confidence: 99%
“…The hydrogen bonding between Arg169 and the carboxyl group is quite strong, as it populates in almost all the snapshots (99.3%) of the basin, which is consistent with the experimental results. 1 There is also a weak hydrogen bond between Thr248 and the carboxyl group, which populates in about one-quarter of the snapshots. For basin A, the substrate can be seen as rotating around its main chain by 180°.…”
Section: Resultsmentioning
confidence: 99%
“…Recent experiments have shown that conformational heterogeneity exists in the Michaelis complex of LDH, 13 and the propensity toward the hydride transfer reaction may vary widely among the different substates of the Michaelis complex. However, the relationship between the substates is still elusive, and the detailed structural features of the substates are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis, by and large, concentrates on the [ 13 C 2 =O] stretch region since the [ 12 C 2 =O] stretch can somewhat couple to other oxamate vibrational modes, distorting the mode pattern. 20 …”
Section: Resultsmentioning
confidence: 99%